Association between physical activity and body mass index with physical fitness in first-year sport students - Yunus, Moch; Hanief, Yulingga Nanda; Sari, Ganis Meinar; Panganiban, Teejay D.; Ferdinandus, Moses Eleazar (CV. Media Digital Publikasi Indonesia, 2023)
This study aims to determine the association between physical activity, Body Mass Index (BMI), and physical fitness in first-year sports students. This study is descriptive quantitative research with a cross-sectional study approach. 66 students (age 18,30 dan 0,70) (male =43, female = 23) of the sport were involved. Instruments to measure physical activity level adopted the Baecke Questionnaire; physical fitness used the sit and reach test, 60-second sit up, 60-second squat thrust, and PACER test. BMI was measured by dividing body weight (kg) by the multiplication of height (meters). Spearman's Rank test was used to determine whether there was a relationship. The results showed that the level of physical activity was mostly in the high category (37.88%), BMI was mostly in the normal category (81.7%), and physical fitness was mostly in the poor category (51.5%). Statistical test results showed that physical activity was related to physical fitness, while BMI was not. In conclusion, a person's level of physical activity can affect physical fitness. Longitudinal studies are needed to ascertain whether physical fitness and physical activity are factors in the success of sports students in following all practice-based courses.